Wage Inequality and Return to Education in Indonesia: Quantile Regression Analysis - Restuning Dyah Widyanti (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2018)
It is essential to the government to recognize the factors causing the increasing trend of income inequality in Indonesia since the Gini coefficient increased between 1996 and 2016. Moreover, wage inequality, which represented by high percentile and low percentile of income, also shows widening gap since 2003. This study focuses on the factors of wage inequality acceleration through the supply side approach that follows the Mincerian wage equation model. Specifically, this paper aims to investigate the association between the return to education and wage inequality in Indonesia. The quantile regression method is applied to compute the return on the investment at different points of the wage distribution. The main finding is that education contributes to an increasing wage inequality due to the significant variation in the rate of return to education in different quantile and as increasing wage dispersion within the same education.DOI: 10.15408/sjie.v7i1.6071